Removal of Arsenite from Water by Iron Modified Activated Carbon Fibre - Li, Fazhan; Li*, Guoting; Wang, Ning; Shao, Jian (Asian Journal of Chemistry, 2013)
Trivalent arsenic is a highly toxic pollutant with carcinogenicity and it is typically detected in ground water. It is most essential to remove As(III) effectively and efficiently before water distribution. In this study, activated carbon fibre was modified with iron salt (FeCl3) by wet impregnation method and used for As(III) removal by adsorption. The morphology of iron modified activated carbon fibre was not altered significantly by SEM measurement. By EDX analysis, the molar ratio of C, Fe and O on iron modified activated carbon fibre was observed to be 92.2, 0.70 and 7.1 %, respectively. The kinetics of adsorption experiment indicated that most of the uptake of As(III) occurred in the first 60 min. Pseudo-second-order model well fitted the kinetics data. The increase of solution pH caused an increase of As(III) adsorption capacity. Ionic strength test indicated that the adsorption process formed inner-sphere complexes. The presence of sulfate, carbonate and nitrate had insignificant influence on As(III) adsorption, while phosphate and silicate hindered the adsorption obviously. The Freundlich equation well described the adsorption isotherm. External electric field was proved to have improved the As(III) adsorption onto the sorbent and helped the desorption of As(III) as well.